2010
DOI: 10.1029/2010jd013884
|View full text |Cite
|
Sign up to set email alerts
|

Multimodel assessment of the upper troposphere and lower stratosphere: Extratropics

Abstract: [1] A multimodel assessment of the performance of chemistry-climate models (CCMs) in the extratropical upper troposphere/lower stratosphere (UTLS) is conducted for the first time. Process-oriented diagnostics are used to validate dynamical and transport characteristics of 18 CCMs using meteorological analyses and aircraft and satellite observations. The main dynamical and chemical climatological characteristics of the extratropical UTLS are generally well represented by the models, despite the limited horizont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 110 publications
3
110
0
1
Order By: Relevance
“…The LMDz-REPROBUS model simulations of stratospheric ozone used to build the climatologies for the IPSL-CM5 for the 1850-2006 period have been evaluated against other chemistry-climate models and a wide range of observations (Jourdain et al 2008;Austin et al 2010a, b;Gettelman et al 2009a, b;Hegglin et al 2010;Morgenstern et al 2010). Figure 5 shows a comparison between the model-calculated and the HALOE (Halogen Occultation Experiment) observation-based annual zonal mean distributions.…”
Section: Stratospheric Ozonementioning
confidence: 99%
“…The LMDz-REPROBUS model simulations of stratospheric ozone used to build the climatologies for the IPSL-CM5 for the 1850-2006 period have been evaluated against other chemistry-climate models and a wide range of observations (Jourdain et al 2008;Austin et al 2010a, b;Gettelman et al 2009a, b;Hegglin et al 2010;Morgenstern et al 2010). Figure 5 shows a comparison between the model-calculated and the HALOE (Halogen Occultation Experiment) observation-based annual zonal mean distributions.…”
Section: Stratospheric Ozonementioning
confidence: 99%
“…The performance of the model was tested against observations and other CCM models [6,[8][9][10][11]. The most extended comparison project was the CCM Validation Activity in two runs (CCMVal-1, CCMVal-2), where 18 leading global CCMs are investigated by several observationally-based performance metrics in order to quantify the ability of models in reproducing the dynamics of stratospheric ozone [12].…”
Section: Introductionmentioning
confidence: 99%
“…The ExTL mean location is centered on the thermal tropopause, but the spread of the ExTL is increased compared to the free-model run. It has been shown that models simulate an ExTL deeper than observed in aircraft measurements, and shifted above the thermal tropopause (Hegglin et al, 2010). This is due to the limited vertical and horizontal resolutions of the models, as well as the lack of representativeness in the aircraft observations.…”
Section: Discussionmentioning
confidence: 88%
“…Studies using in situ aircraft measurement show that the ExTL is centered on the thermal tropopause with a narrower extent than observed in this study (Pan et al, 2004(Pan et al, , 2007. In a multi-model assessment, Hegglin et al (2010) showed that models simulate an ExTL that is wider than observed in satellite observations, and shifted above the thermal tropopause. The low vertical resolution (800 m) in the model UTLS layers and also the low horizontal resolution (2 • × 2 • ) used in this study is not sufficient to represent the sharp gradients of O 3 and CO observed at Table 2) but a lower mean value of about 0.45 km.…”
Section: Diagnostic 3: Sharpness Of the Transitionmentioning
confidence: 80%
See 1 more Smart Citation